RANCANG BANGUN E-COMMERCE PENJUALAN BUAH MENGGUNAKAN METODE CUSTOMER RELATIONSHIP MANAGEMENT (CRM) - Laras Avisya (LPPM Politeknik Jambi, 2023)
Fruit is one of the horticultural crops that plays an important role in improving the quality of nutrition for humans. Fruit also contains many vitamins and minerals that are beneficial to human health. One complete Fruit Shop in providing fresh fruit is